Sculpture in the Philippines from Anito to Assemblage and other essays - Guillermo, Alice; Jose, Regalado Trota; Pilar, Santiago A.; Javelosa, Jeannie E.; Roa, Lourdes Ruth R.; Alvina, Corazon S. (Manila Metropolitan Museum of Manila, 1991)
Complements the exhibition "Iskultura" on the occasion of the birth centenary of Guillermo Tolentino, the first Philippine National Artist for Sculpture.
Sculpture in the Philippines / by Alice G. Guillermo -- Styles in Philippine retablos / by Regalado Trota Jose -- Philippine secular sculpture / by Santiago A. Pilar -- The public sculptural tradition / by Jeannie E. Javelosa -- Mortuary art / by Lourdes Ruth R. Roa and Corazon S. Alvina.
"Published on the occasion of the exhibition 'ISKULTURA: from anito to assemblage' 15 June 1991 until 15 August 1991, organized by Metropolitan Museum of Manila"--Title page verso.
Keywords: Sculpture -- Philippines; Sculpture